Langkah CERIA “Cegah Remaja dari Anemia” dengan Buku Saku Isi Piringku - Anik Nur Laili (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
The prevalence of anemia of adolescent girls in DIY in 2018 was 36% while the prevalence at the Yogyakarta City level reached 35.2%. The high rate of anemia among adolescents is a factor in the decrease in learning concentration which results in learning achievement. One way for students to prevent anemia is by the CERIA step